Semangat Pelayanan Santa Teresa dari Calcutta Menjadi Inspirasi Bagi Katekis Masa Kini - Megawati Naibaho; Sitepanus Zebua; Rosmeidar Laia (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2024)
St. Teresa of Calcutta was a Religious who had a strong faith and love for the poor. She is one of the figures in the Catholic Church who has been canonized a saint. The purpose of this writing is to study the life and charism of St. Teresa of Calcutta who lived her faith in God which was manifested in her service to the poor. The method used to explore this theme is a literature review. The authors have tried to explore matters related to St. Teresa and her service through reliable sources. Through this writing have findings were obtained about the life and work of St. Teresa's of Calcutta. The exemplary and attitude of St. Teresa's life are figures for catechists for their work and service. Catechists need to live the values ​​of Evangelical spirituality as lived by St. Teresa of Calcutta. This writing can inspire catechists to develop spiritual values ​​that are rooted in a strong faith in God that manifests itself in concrete actions. The implications of writing St. Teresa can be an inspiration and example for catechists to be closer to God, faithful in their duties and service.